Ensino de biologia evolutiva: uma abordagem investigativa por meio de um clube de ciências - Batista, Paloma Nair Gomes (2024)
The pedagogical approach of inquiry-based learning, which encourages active learning and solving real-world problems through scientific investigation, can be incorporated into Basic Education through Science Clubs. These clubs are pedagogical spaces that promote teamwork, the development of important social skills, as well as scientific and practical knowledge through experimentation. With the approval of the National Common Curricular Base (BNCC) in 2017, high school education began to have a more "flexible" curriculum with the inclusion of Formative Itineraries, reducing the total workload of general education subjects, including Biology. Given this scenario, this work aimed to understand the role of the Science Club, based on elements of inquiry-based learning, as a favorable place for teaching Evolution and enhancing the development of epistemic practices. Evolutionary Biology arouses great curiosity and questions among students, and the reduced workload of the Biology subject is not sufficient to address it adequately. The results reveal the success of implementing the Science Club as an elective course, highlighting not only the participants' engagement during the process but also the development of epistemic practices of proposing, justifying, evaluating, and legitimizing during investigative interventions, thus favoring the learning about Evolution.